Influences : art, optics, and astrology in the Italian Renaissance - Quinlan-McGrath, Mary (University of Chicago Press, 2013)
Today few would think of astronomy and astrology as fields related to theology. Fewer still would know that physically absorbing planetary rays was once considered to have medical and psychological effects. But this was the understanding of light radiation held by certain natural philosophers of early modern Europe, and that, argues Mary Quinlan-McGrath, was why educated people of the Renaissance commissioned artworks centered on astrological themes and practices. Influences is the first book to reveal how important Renaissance artworks were designed to be.